(3RGO GdeSGaQ aj eYQaI aVd GdOGFQs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI dWjaI ai eYQaI hVY NWhW aVd GdOGFQ Ydi GdHSGFW hGdbGFeGJ hGdeGFdGJ dNUJgG ai cJGHi GdeSei HEQTGO GdMGFQ Edi eYQaI hVY NWhW aVd GdOGFQ s
(3BNQgG (B:s
(3aMUd XdgG GdeHShW hced HgG GdYed ceG JbOe jMUd ebOGQ GdSeJ JMJ GdeQcR hLgJg Lgg GdHYO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B61 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B947s
Keywords: (3Gdadcs